(untitled) (Revista Archai, 2019)
This article deals with the relationship between simple, monadic, divine words and the words of men linked to corporeity, devoid of clarity and univocity. For the divine word to be grasped by men a kind of transformation is necessary. One can hypothesize the existence of an archetypal, primordial language, in imitation of the essence of things. It is the language of Adam: given the perfection of a still pure soul, not affected by infirmity, illness or passion, the progenitor seized immediate impressions, grasped the meaning of things whose natures could be enunciated and thought at the same time. It is the original perfect language and is perhaps common to humans and animals if in the Garden of Eden the words of the serpent were understood by Eve. A distinction is drawn between the language of Adam, mimetic of the language of God and the mosaic language in which we have the translation of the divine word in human language. This, despite that, for Moses too it is said that the names correspond to the description of things. A further passage takes place with the passing from one language into another. God addresses different kinds of communication to different people according to their capacities. It is a “translation” of a noetic language that can speak monadically ”“ and it is the case of communication to Moses ”“ or assume the form of names and verbs proper to human language ”“and it is what happens with the Septuagint, translators like Aron.